Nanostructured lipid carriers and their potential applications for versatile drug delivery via oral administration - Nguyen, Van Hong; Thuy, Vy Nguyen; Van, Toi Vo; Dao, Anh Hoang; Lee, Beom Jin (OpenNano, 2022)
Enteral administration is the most convenient route despite the gastrointestinal physiological barriers. Nanostructured lipid carriers (NLCs) have emerged as a promising strategy for improving therapeutic compound oral bioavailability, not only due to nanomaterial advantages, but also due to lipid ingredients themselves, such as preventing enzyme degradation, taste masking, and especially favorable uptake by chylomicron pathways to the lymphatic drainage system. Therefore, NLCs have been employed for systemic absorption improvement, site-specific treatment of the digestive system, and especially targeting delivery to the liver, brain, cancer ulcer, and so on through oral uptake. Lipids, surfactants, and other materials like lipophilic counter ions or coating polymers are considered for oral NLCs formulation design. A variety of NLCs fabrication methods and stability enhancement techniques by transforming NLCs into powder form or hydrophobic -ion pairing are discussed. Hence, this review aims to provide an overview of the current state of the art of NLCs and their modern techniques and applications in oral drug administration, which will advocate their extended use in the future.
Keywords: Hydrophylic ion pairing; Nano lipid carrier; Oral administration; Site specific; Targeting